JESD 2021
DOI: 10.7176/jesd/12-4-07
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Engagement and Performance of Community Based Conservation Projects: A Case of Laikipia Conservation Region Conservancies

Abstract: This study examined the influence of stakeholder engagement on the performance of Community Based Conservation (CBC) projects in Kenya. Guided by theory of change, participatory development and stakeholder theories, the philosophical underpinning employed was pragmatism where cross sectional study design that adopted convergent mixed methods approach composed of quantitative and qualitative strands was utilized. Questionnaires, focused group discussions and document analysis were used to collect data from seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Once decisions are made on who to involve and to what extent, one needs a set of appropriate tools for stakeholder involvement: interviews, feedback sessions and dialogue (Islam et al, 2020). In their study, Ndonye et al (2021) used the same framework in assessing stakeholder engagement and performance of community‐based conservation projects in Laikipia Conservation Region Conservancies in Kenya. They observed that conservation projects do not exist in isolation; rather, they operate within a local context populated by communities who hold vested interests in the outcomes of such projects.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Once decisions are made on who to involve and to what extent, one needs a set of appropriate tools for stakeholder involvement: interviews, feedback sessions and dialogue (Islam et al, 2020). In their study, Ndonye et al (2021) used the same framework in assessing stakeholder engagement and performance of community‐based conservation projects in Laikipia Conservation Region Conservancies in Kenya. They observed that conservation projects do not exist in isolation; rather, they operate within a local context populated by communities who hold vested interests in the outcomes of such projects.…”
Section: Theoretical Frameworkmentioning
confidence: 99%